Fodor's Puerto Rico - Barrier, Brooke; Fodor's Travel Publications, Inc. (New York : Fodor's Travel, 2008)
A comprehensive travel guide to Puerto Rico, with maps and information on accommodations and restaurants, shopping and entertainment, and other interesting sites.
Includes index.
Young Adult
Keywords: Puerto Rico -- Guidebooks; Puerto Rico -- Guidebooks